2006
DOI: 10.1136/vr.158.12.393
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of bluetongue virus in Kosovo between 2001 and 2004

Abstract: In 2001, clinical cases of bluetongue were observed in Kosovo, and in that year and in 2003 and 2004, serum samples were collected from cattle and small ruminants and tested for antibodies to bluetongue virus. The results provide evidence that bluetongue virus was not present in Kosovo before the summer of 2001, but that the virus circulated subclinically among the cattle and sheep populations of Kosovo in 2002, 2003 and 2004.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
2
11
0
Order By: Relevance
“…This report describes the first evidence of BTV-4 in sheep in Kosovo as well as BTV seroprevalence in domestic rumi-nants in years 2014 and 2015. After the first BT disease outbreak reported in 2001 caused by BTV serotype 9 (Osmani et al, 2006), in disease outbreak in 2014 in Kosovo the results of this study confirmed high seroprevalence in domestic ruminants of 11.6%: 8.3% in sheep, 19.1% in goats and 19.1% in cattle. The RT-PCR analysis in samples from sheep with clinical signs confirmed presence of BTV se- Rodriguez-Sanchez et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This report describes the first evidence of BTV-4 in sheep in Kosovo as well as BTV seroprevalence in domestic rumi-nants in years 2014 and 2015. After the first BT disease outbreak reported in 2001 caused by BTV serotype 9 (Osmani et al, 2006), in disease outbreak in 2014 in Kosovo the results of this study confirmed high seroprevalence in domestic ruminants of 11.6%: 8.3% in sheep, 19.1% in goats and 19.1% in cattle. The RT-PCR analysis in samples from sheep with clinical signs confirmed presence of BTV se- Rodriguez-Sanchez et al, 2008).…”
Section: Discussionsupporting
confidence: 68%
“…Multiple BTV serotypes (serotypes 1, 2, 4, 6, 8, 9, 11 and 16) have in-vaded Europe since 1998 Rodriguez-Sanchez et al, 2008). Bluetongue disease with clinical signs was reported in Kosovo in 2001, caused by BTV-9 serotype (Osmani et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Over the following 3 years, this strain, identified as BTV-9, spread northwards and westwards through mainland Greece and beyond, eventually reaching as far as Kosovo in 2001 (Osmani et al 2006). This was followed by incursions of BTV4 and BTV-16 in 1999 and BTV-1 in 2001 into mainland Greece.…”
Section: -2005: Emergence Of Bluetongue Virus In Southern and Easmentioning
confidence: 99%
“…Once monthly datasets were incorporated into the map, smoothing out was performed through kriging, apart from the altitude map which was derived from an elevation model. Suitability categories, based on Culicoides obsoletus group biology and habitat data [ 1 , 6 , 7 , 26 - 28 ], were used to reclassify the output values, in order to grade all monthly maps on a standard scale, as done for the R 0 values mentioned above. The 'environmental envelope' of the Obsoletus group of Culicoides was concentrated upon in contrast to the classical Old World vector C. imicola , due the fact that the former is the most abundant group caught in the Swiss entomology surveillance program [ 9 ] and has been shown to transmit BT virus in other countries [ 3 ].…”
Section: Methodsmentioning
confidence: 99%